University Web Site Content Benchmarking : Evaluation and Improvement - Yew, Been Hui (2003)
Web sites serve many kinds of purposes vary from entertainment, informational to promotional. University web sites serve informational and educational purposes. However, the quality of information in the web site is subjected to reliability, accuracy, and value issues. Thus, this study attempts to evaluate the content of the School of Information Technology web site compared to web sites of related universities by using benchmarking approach. The objectives of this study were to evaluate the quality of the content provided in the web site, to gather a set of evaluation criteria in term of content evaluation, and to propose the appropriate or benchmark content for STM’s web site. This study was done based on the benchmarking framework model from Misic & Johnson (1999). Questionnaire has been used as a research instrument to conduct the survey. The participants of this study involved representatives for each category of users ranging from student to staff of UUM. The findings have significantly identified the strengths and weaknesses of all web sites. Furthermore, the most startling result revealed that most of the web sites including STM’s web site of UUM suffered severe problems in the authority, currency, and coverage aspects. Nevertheless, in terms of accuracy and objectivity, all web sites scored well. Furthermore, the results show how benchmarking was used to measure the quality of content of the web sites, and provides suggestions for content improvement. Consequently, benchmarking approach had provided a measure of how STM’s web site compared to others by using a set of comprehensive criteria, and identify the drawbacks and strengths of STM’s web site and others as well in order to propose the most appropriate content features. The outcome of this study has significantly provides a basis for future studies in web evaluation for benchmarking other aspects in university’s web site and other types of web sites as well.